41. New perspectives on the Mesolithic of the Sado Valley (southern Portugal): Preliminary results of the SADO MESO project - Arias, Pablo (2021)
The lower Sado Valley in southern Portugal is one of the most important concentrations of Mesolithic settlements in Europe. Moreover, many of the sites included cemeteries, which have provided valuable information on mortuary practices of the last hunter-gatherers in southern Iberia and a very important sample of human remains. Despite the development of large systematic excavations in the mid-twentieth century and recent attempts to re-examine some sites, only very partial information was available. Yet, there are rich unpublished archaeological collections in the National Museum of Archaeology in Lisbon, and the preservation of most of the sites is quite satisfactory. Since 2010, a Luso-Spanish interdisciplinary team has systematically been re-appraising this area within the framework of COASTTRAN , CoChange, and SimTIC – three successive research projects on the transition to the Neolithic in coastal areas of south-western Atlantic Europe and the development of symbolic thought in the late Upper Palaeolithic and Mesolithic. The project design and preliminary results of the first six fieldwork seasons are presented in this paper.